(untitled) (Altre Modernità, 2014)
“In the late 1980s, Nelson Mandela stood alone against the apartheid state.” This comment taken from the DVD Box set cover of Nelson Mandela: From Freedom to History summarises the approach taken by many of the cinematic and televisual representations of Mandela. Linked with this is a statement by the CEO of Marriott which speaks of Mandela as “an individual who changed the arc of history through his or her singular contribution, not as a function of the era or the movement but because of what they did alone.” Together, these descriptions attempt to appropriate Mandela for a sanitised version of western individualism which sees him variously as a liberal icon, saintly hero, or the celebrity one-off “magic negro”, in Okwongo’s damning phrase taken from his magisterial valedictory piece “Mandela will never, ever be your minstrel” (Okwongo 2013). In the process, Mandela’s role in the anti-apartheid...